FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN PENYAKIT PARU OBSTRUKTIF KRONIK (PPOK) PADA PASIEN POLIKLINIK PARU DI RSUD MEURAXA - Nurfitriani Nurfitriani; Devi Mulia Ariesta (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Chronic obstructive pulmonary disease (COPD) is a disease characterized by obstruction of air flow in the airways that is not completely reversible persial. The World Health Organization (WHO) through the Global Burden of Disease Study reports that the prevalence of 251 million COPD cases worldwide occurred in 2016. Several risk factors that cause COPD include smoking, air pollution, occupation, family history, age, gender and status social economy. COPD is a non-communicable disease that is often found in cases of lung disease. Knowing the prevalence and relationship of age and gender on COPD events in the Meuraxa Lung Polyclinic. Descriptive analytic research with a cross-sectional study design. The sampling technique uses total side techniques. The total sample of 1,241 respondents consisting of 294 respondents who were diagnosed with COPD and 947 respondents who were not diagnosed with COPD. Data analysis was performed univariately and bivariately using the chi-square test. The results of bivariate analysis for age obtained p value = 0,000 (p 0.05) and in the gender obtained p value = 0,000 (p 0.05). These results indicate that there is a statistically significant relationship between age and gender on COPD events in patients at the Meuraxa Pulmonary Hospital, Banda Aceh.Keywords: COPD, age, gender